Selective internal radiation therapy for liver tumours - Sundram, Francis X (Clin Med (Lond), 2017)
Primary and secondary liver malignancies are common and associated with a poor prognosis. Surgical resection is the treatment of choice; however, many patients have unresectable disease. In these cases, several liver directed therapies are available, including selective internal radiation therapy (SIRT). SIRT is a multidisciplinary treatment involving nuclear medicine, interventional radiology and oncology. High doses of localised internal radiation are selectively delivered to liver tumour tissues, with relative sparing of adjacent normal liver parenchyma. Side effects are minimal and radiation protection measures following treatment are straightforward. In patients who have progressed following chemotherapy, clinical trials demonstrate prolonged liver progression-free survival. SIRT is offered at 10 centres in England via the NHS England Commissioning through Evaluation programme and is approved by the National Institute for Health and Care Excellence for certain liver malignancies. SIRT holds unique promise for personalised treatment of liver tumours.